The Changes of Settlement Types in the Kajang Area: from Segmentary Society to Chiefdoms - Erni Erawati (Universitas Airlangga, 2022)
This study aims to reveal the current type of community in Kajang area based on social structure, politics, economy, technology, as well as ideology. Kajang area is a traditional region located on the hill sides of Bone Bay Sea shore in the District of Kajang, Bulukumba, South Sulawesi Province. To pursue the aim of this study, descriptive qualitative method is used. The results show that historically, in order to overcome the limitations of facilities and infra structure, communities in Kajang reached other regions either by land or water. Thus, there are various artifacts from megalithic and Islamic cultures indicating the existence of local cultural syncretism with the culture from other regions. All of the artifacts found in Kajang area are bound in a functional fabric, which is limited by the level of supporting human activities, namely community protection activities, religious and ceremonial activities, as well ashousehold activities. Besides, relics found also indicate that there was a cultural shift in Kajang region, from agrarian culture to maritime one. Thus, the current type of community in Kajang area can be considered to be shifted from segmentary society to chiefdom. Nevertheless, this does not mean that with the emergence of chiefdoms, the segmentary society has simply disappeared.